2009
DOI: 10.1364/oe.17.014780
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative optical tomography of sub-surface heterogeneities using spatially modulated structured light

Abstract: We present a wide-field method for obtaining three-dimensional images of turbid media. By projecting patterns of light of varying spatial frequencies on a sample, we reconstruct quantitative, depth resolved images of absorption contrast. Images are reconstructed using a fast analytic inversion formula and a novel correction to the diffusion approximation for increased accuracy near boundaries. The method provides more accurate quantification of optical absorption and higher resolution than standard diffuse ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
110
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 26 publications
0
110
0
Order By: Relevance
“…It is based on diffuse optical spectroscopic principles and is well-suited for quantitative imaging of tissue [21][22][23][24][25][26][27][28]. This non-contact, in-vivo technique provides quantitative, spatial maps of tissue optical properties and biochemical composition for fields of view over 100 cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It is based on diffuse optical spectroscopic principles and is well-suited for quantitative imaging of tissue [21][22][23][24][25][26][27][28]. This non-contact, in-vivo technique provides quantitative, spatial maps of tissue optical properties and biochemical composition for fields of view over 100 cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…To improve on these shortcomings, NIRS undergoes a transition from a single-point technique employing one or several source-detector pairs towards an optical mapping technique by applying, first of all, large arrays of source-detector pairs [9]. Secondly, two-dimensional (2D) imaging approaches are realized in a variety of different methods, ranging from structured illumination combined with frequency-domain NIRS [10][11][12][13] to flying-spot scanning methods [14]. These imaging approaches have already been applied to a variety of tasks, such as measuring optical properties of different types of phantoms and biological tissue [10,12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, two-dimensional (2D) imaging approaches are realized in a variety of different methods, ranging from structured illumination combined with frequency-domain NIRS [10][11][12][13] to flying-spot scanning methods [14]. These imaging approaches have already been applied to a variety of tasks, such as measuring optical properties of different types of phantoms and biological tissue [10,12,15,16]. There is a general trend towards non-contact techniques, thereby eliminating all sensor-tissue contact problems characteristic of the conventional fiber-optode based NIRS equipment.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, digital micromirror devices (DMDs), able to project any pattern of light onto a sample, have been involved in imaging [1] and tomographic schemes [2][3][4][5]. Fast algorithms able to deal with very large datasets have been proposed for this modality [6,7], and it was observed that a limited number of patterns can be used in contrast to a large number of point-source illuminations. In parallel, the concept of data compression based on Fourier [8] or wavelet encoding [9,10] has been recently applied to CCD measurements acquired with point sources, in order to reduce the computational size of the problem.…”
mentioning
confidence: 99%